Forums Assignment Help The statement is equivalent to

Viewing 3 posts - 1 through 3 (of 3 total)
  • Author
    Posts
  • #1928
    john Smith
    Participant

    The statement p → (q → p) is equivalent to

    (a) p → (p → q)

    (b) p → (p ∨ q)

    (c) p → (p ∧ q)

    (d) p → (p ↔ q)

    #10513
    ahprofessional
    Participant

    Answer: (b) p → (p ∨ q)

    #10530
    Aakanksha
    Participant

    nice one

Viewing 3 posts - 1 through 3 (of 3 total)
  • You must be logged in to reply to this topic.